The geology of Cape Breton Island, Nova Scotia [electronic resource] - Gilpin, Edwin, 1851-1907 ([London? : s.n., 1886)
Caption title. "From the Quarterly Journal of the Geological Society for November 1886." Electronic reproduction. Mode of access: Internet. 44